2016
DOI: 10.1016/j.jce.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Creative accounting and electoral motives: Evidence from OECD countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
12

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 50 publications
1
23
0
12
Order By: Relevance
“…Typically the residual is small, but occasionally it can be big. The literature has documented that creative accounting can inflate the residual near election time or when the economy enters a slump (Reischmann, 2016). In Europe, there is also evidence of a persistent positive residual in the nineties when EU rules kicked in (see Alt et al, 2014 for evidence on this point).…”
Section: Fiscal and Financial Factsmentioning
confidence: 99%
“…Typically the residual is small, but occasionally it can be big. The literature has documented that creative accounting can inflate the residual near election time or when the economy enters a slump (Reischmann, 2016). In Europe, there is also evidence of a persistent positive residual in the nineties when EU rules kicked in (see Alt et al, 2014 for evidence on this point).…”
Section: Fiscal and Financial Factsmentioning
confidence: 99%
“…Third, the governance structure of public sector entities will often differ considerably from a private corporation, leading to different costs and incentives. There may be short-term political incentives to cheat, particularly before elections, which outweigh longer-term detriments (Reischmann, 2016). There may be few with sufficient knowledge or incentives to monitor public sector financial statements in detail, so that the likelihood of getting caught is low.…”
Section: Public Sector Creative Accounting: the Broad And Focused Viewsmentioning
confidence: 99%
“…However, Seiferling (2013) found that there was no significant variance between SFA and fiscal transparency once controlled for banking crises, inflation and fiscal rules. There is some evidence that SFA increase in the year of elections (Buti et al, 2007), while Reischmann (2016), examining OECD countries up to 2011, found evidence that SFA are used strategically before regular elections to hide or reduce reported budget deficits.…”
Section: Reporting Deficits and Debt In The Context Of Emu And Sgpmentioning
confidence: 99%
“…11 If state governments change the constitution to comply with the debt brake, they indicate that they seriously want to consolidate their budgets. 12 Constitutional debt brakes may, however, still contain loopholes, for example, by leaving out special funds and public enterprises (Ciaglia et al, 2012;Heun, 2013;Reischmann, 2014Reischmann, , 2015.…”
Section: German Debt Brakementioning
confidence: 99%